High-throughput implementation of the RIPEMD-160 - Kakarountas, Athanasios P.; Michail, Harris; Goutis, Costas E.; Rjoub, Abdoul M. (My University, 2009)
One-way hash functions are the main cryptographic primitives which are used in the network protocols for user authentication and message integration. In the literature, implementations have been proposed either in hardware or software. The rich number of implementations is expected considering the number of constraints of a target application. When the target is to service more and more users-clients and thus the increase of their throughput, a hardware implementation is dictated. In this paper, RIPEMD-160 hash function is considered and a technique to increase its throughput. This technique involves the application of algorithmic transformations in space and time. The proposed technique leads to an increased throughput by 35% when compared to conventional implementations. Copyright © 2009 Inderscience Enterprises Ltd.
Keywords: Security; CMAC; Message authentication code; Secured transactions; VLSI implementation